A Postcolonial Analysis Of Advertisements In The British North Borneo Herald - Abdul Rahim, Anis (2022)
Now known as Sabah, North Borneo was under the British administration from 1881 until 1963. The British North Borneo Herald was published by The British North Borneo (Chartered) Company and circulated from 1883 until 1941. This study discussed the relationship between advertising, consumerism, and text production by utilising The British North Borneo Herald advertisements. The objectives of this research are to examine the meanings of the text in the selected colonial advertisements found in The British North Borneo Herald; to ascertain the ideology of consumerism in the selected colonial advertisements found in The British North Borneo Herald in a colonial environment, and to study the relationship between the ideology of consumerism and the production of text through Eagleton’s Materialist Criticism. Thirty-four advertisements, published between 1937-1941, were selected based on four criteria: the advertisements must have both visual and body copy; the advertisements were selected from the last five years of The British North Borneo Herald publication; the products advertised were originated from Britain and its allies, and the advertisements chosen promote essential and luxury products. Two types of analysis were utilised for this study: social semiotic analysis (Halliday’s Transitivity Model (2004) and Kress and van Leeuwen’s Grammar of Visual Design (1996/2006)) and Marxist analysis (Eagleton’s Materialist Criticism (1978)). Based on the semiotic analysis on 34 advertisements, there are three categories of needs and desires: health, lifestyle, and relationship.